Sustainable Finance and Ethical Investment: A Paradigm Shift in Global Capital Markets - Sandra, Jana; Malik, Deni; Pratiwi, Sekar Widyastuti; Dameria, Rina (Jurnal Informatika Ekonomi Bisnis, 2025)
This study presents a comprehensive literature review on the evolving role of sustainable finance and ethical investment as a transformative force in global capital markets. It explores the theoretical foundations that underpin ethical investing, including stakeholder theory, institutional theory, legitimacy theory, and behavioral finance. The review identifies key drivers of ethical investment, such as regulatory developments, institutional investor demand, technological innovation, and changing demographic preferences. Empirical findings indicate that sustainable investment strategies often yield comparable or superior financial performance while enhancing portfolio resilience. However, persistent implementation challenges-including inconsistent ESG metrics, greenwashing, and measurement limitations-undermine the credibility and effectiveness of ethical finance. The study highlights the need for greater standardization, reliable data, and regulatory coherence to support the sustainable integration of ESG principles into financial systems. Future research directions are proposed to deepen the understanding of ESG impact, investor behavior, and technological applications in responsible investing.